2003
DOI: 10.1046/j.1472-765x.2003.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of an extracellular polysaccharide produced by Bacillus sp. CP912

Abstract: Aims: In this study, some physical properties of Bacillus sp. exo-polysaccharide were investigated. Methods and Results: An extracellular polysaccharide was purified by sequential precipitations after homogenization of the diluted culture supernatant of Bacillus sp. CP912. Its physical properties were examined such as lipid emulsifying effect on several vegetable oils and flocculating activity against the activated carbon suspension. The melting point and endothermic calories of the polysaccharide were 128AE7°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 19 publications
4
19
0
Order By: Relevance
“…Glucomannan was used in the laboratory production of creamy products tested for stability at different temperatures with a view to their application in the cosmetics industry (8). Similar results were obtained by Yun and Park (15), who showed that an extracellular polysaccharide synthesised by Bacilus sp. СР912 had a high emulsifying activity for oil/water emulsions with different vegetable oils.…”
Section: Final Remarkssupporting
confidence: 57%
See 1 more Smart Citation
“…Glucomannan was used in the laboratory production of creamy products tested for stability at different temperatures with a view to their application in the cosmetics industry (8). Similar results were obtained by Yun and Park (15), who showed that an extracellular polysaccharide synthesised by Bacilus sp. СР912 had a high emulsifying activity for oil/water emulsions with different vegetable oils.…”
Section: Final Remarkssupporting
confidence: 57%
“…In most of the experiments, the separated oil phase percentage was zero, whereas the intact emulsion percentage was 100 or close to this value. the lipid emulsifying effect of the synthesised ePS alone and in combination with the food additives was evaluated through the centrifugation test at a relatively low speed of 2 000×g for 5 min as described by Yun and Park (15), as percentage of the emulsion layer and the entire emulsion system. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Yun and Park used an extracellular polysaccharide synthesized by Bacillus sp. to obtain emulsions which had a stronger emulsifying effect than those made with xanthan [26]. Therefore, it was necessary to study the effect of some hydrocolloids on the emulsifying and stabilizing properties of the investigated biopolymer.…”
Section: Referencesmentioning
confidence: 99%
“…Polysaccharides synthesized by microorganisms have been extensively applied as emulsifiers, stabilizers, binding and gelling agents, coagulants, thickeners, and suspending agents in different areas [23][24][25][26]. Little information on polysaccharides produced by psychrophilic yeast and their physicochemical properties is available in the literature [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated OPR m a x was 83 mg L − 1 h − 1 or 51.5 μmol O 2 g −1 biomass min −1 ; its performance was comparable with photosynthetic activities of other non-extremophile microalgae strains. For example, the OPR for Chlorella vulgaris was 78 μmol O 2 g −1 biomass min −1 (Yun and Park 2003;Wang et al 2014) and 46 μmol O 2 g −1 biomass min −1 for Scenedesmus almeriensis (Costache et al 2013). …”
Section: Discussionmentioning
confidence: 99%